2019
DOI: 10.1080/10705511.2019.1620109
|View full text |Cite
|
Sign up to set email alerts
|

Model Fit Estimation for Multilevel Structural Equation Models

Abstract: Structural equation modeling (SEM) provides an extensive toolbox to analyze the multivariate interrelations of directly observed variables and latent constructs. Multilevel SEM integrates mixed effects to examine the covariances between observed and latent variables across many levels of analysis. However, while it is necessary to consider model fit, traditional indices are largely insufficient to analyze model fit at each level of analysis. The present paper reviews i) the partially-saturated model fit approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…In line with our hypotheses, a PA and NA structure fit the data better than a single valence factor or two orthogonal factors in all cases, thereby offering support for previous findings from both diary and ESM data (Rappaport et al, 2019;Rush & Hofer, 2014;Viechtbauer et al, 2020). The high correlation of PA and NA at the WP level of the short questionnaire indicated a high degree of redundancy between the two factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our hypotheses, a PA and NA structure fit the data better than a single valence factor or two orthogonal factors in all cases, thereby offering support for previous findings from both diary and ESM data (Rappaport et al, 2019;Rush & Hofer, 2014;Viechtbauer et al, 2020). The high correlation of PA and NA at the WP level of the short questionnaire indicated a high degree of redundancy between the two factors.…”
Section: Discussionsupporting
confidence: 90%
“…Studies that were able to distinguish the WP and BP structure of affect have come to varying conclusions. Generally, a two-factor structure with correlated PA and NA showed adequate fit (Brose et al, 2015;Merz & Roesch, 2011), and fit better than a model with a single valence factor (Rappaport et al, 2019;Rush & Hofer, 2014;Viechtbauer et al, 2020) at both levels. Several studies also observed different correlations between PA and NA at the different levels of analysis (Bleidorn & Peters, 2011;Rush & Hofer, 2014;Schmukle et al, 2002).…”
Section: Affective Structure Across Esm Protocolsmentioning
confidence: 93%
“…Studies that were able to distinguish the WP and BP structure of affect have come to varying conclusions. Generally, a two-factor structure with correlated PA and NA showed adequate fit (Brose et al, 2015;Merz & Roesch, 2011), and fit better than a model with a single valence factor (Rappaport et al, 2019;Rush & Hofer, 2014;Viechtbauer et al, 2020) at both levels. Several studies also observed different correlations between PA and NA at the different levels of analysis (Bleidorn & Peters, 2011;Rush & Hofer, 2014;Schmukle et al, 2002).…”
Section: Affective Structure Across Esm Protocolsmentioning
confidence: 99%
“…Agricultural carbon emission mainly comes from farmland utilization, paddy field, livestock intestinal fermentation and manure management. Among them, agricultural land use carbon emissions (farmland ecosystem carbon emissions), accounted for 34.29% of the total agricultural carbon emissions [ 10 ]. In order to explore the path of agricultural sustainable development, scholars have done a lot of research on the influencing factors of agricultural carbon emissions, it involves different countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly decomposition model of carbon emission factors includes LMDI decomposition method, Kaya identities and STRIPAT model [ 1 , 9 , 10 ]. Most of study found that, GDP of planting industry, GDP of agriculture, regional GDP, total regional population and total rural population, agricultural production efficiency, agricultural industrial structure, industrial structure, regional economic development level, urbanization all of the factors have reflected the influencing factors of agricultural carbon emissions [ 4 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%